ANALISIS KEMAMPUAN PEMECAHAN MASALAH BERDASARKAN TINGKAT KEMAMPUAN MATEMATIKA - Sri Surya Sasih; Harry Soeprianto; Sudi Prayitno (FKIP Universitas Mataram, 2022)
This study aims to determine the ability of problem solving in the material system of two variables linear equations based on the level of mathematical ability of students categorized in 3 levels, namely high, medium and low. In addition, it was also to find out the problem-solving ability for each step of the solution. The population in this study was students of class VIII SMP Negeri 7 Mataram, with a sample of class VIII.B. Where the sampling technique was done by researcher based on certain considerations that best meet the information needed in research. This type of research was qualitative descriptive study. The results showed that students with high mathematical ability had an average problem solving ability of 66.2 with good criteria. Students with moderate mathematical ability had an average problem solving ability of 58.0 with sufficient criteria. Students with low levels of mathematical ability had an average problem solving ability of 40.5 with low criteria. The average problem solving ability of students was 56.3 with sufficient criteria.